Effect of nipa palm (Nypa fruticans Wurmb.) vinegar on the incretin hormones and intestinal glucose transporters in type 2 diabetes mellitus rat model - Nur Izzati Razali; Tri Widyawati; Dwi Rita Anggraini; Vuanghao Lim; Nor Adlin Yusoff (BMC Complementary Medicine and Therapies)
Abstract Nipa palm vinegar has been traditionally used to lower blood glucose levels by diabetic patients. This study aims to analyse the effect of aqueous extract (AE) of nipa palm vinegar on glycemic parameters and glucose transporter-incretin hormonal system in type 2 diabetic rat. The model was established using a combination of high-fat diet (p.o.) and low dose streptozotocin (i.p.). AE (250, 500, and 1000 mg/kg) was administered orally once daily for 28 days. Biochemical parameters related to type 2 diabetes including fasting glucose, serum insulin, lipid profiles, incretin hormone, liver, and pancreatic histology were evaluated. Relative expression of jejunal glucose transporters was also determined. Induction of diabetes caused significant (p = 0.026) weight loss, hyperlgycemia, hypoinsulinemia, dyslipidemia and reduced incretin hormones. Diabetes onset also disturbed HOMA-IR and HOMA-ß cell function indices, altered the morphological features of hepatocytes and pancreatic islet and overexpressed intestinal glucose transporters, SGLT1 and GLUT2. Repetitive oral administration of AE (1000 mg/kg) for 28 days ameliorated the biochemical abnormalities and improved HOMA-β cell function of diabetic rats. Histological studies revealed AE treatment preserved the integrity of pancreatic islet and protected hepatocytes from degeneration and atrophic effects of streptozotocin. Further analysis suggested the effect of AE in stimulating incretin hormones secretion via the action of DPP4 inhibitor and by modulating jejunal SGLT1 expression. In conclusion, the study suggested AE exerted its antidiabetic effect partially by stimulating insulin secretion via incretin hormone and intestinal glucose transporter pathway.